A pole piece and a lithium ion battery
By setting a protective layer on the current collector surface of the lithium-ion battery electrode sheet, using a combination of high-content inactive materials and conductive agents, combined with carbon-coated inorganic particles, the safety and electrical performance of lithium-ion batteries during mechanical damage are solved. Problem, achieving higher safety and electrical performance.
Patent Information
- Application Number
- CN202111434303.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-29
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-11-29
AI Technical Summary
Lithium-ion batteries are prone to internal short circuits during mechanical damage, release a large amount of heat and cause fire failure, and the prior art is difficult to take into account both battery safety and electrical performance.
Design an electrode sheet, including a substrate and a protective layer on the surface of the current collector, consisting of 62%-96% of inactive material, 0.1%-8% of conductive agent and 3%-30% of binder. And coat the surface of the inorganic particles to ensure that the mass of the carbon layer is less than 10% of the mass of the inorganic particles to build a comprehensive conductive network.
Effectively improve the safety of lithium-ion batteries, reduce the probability of fire failure, improve the pass rate of nail penetration test, and keep the electrical performance basically unaffected, solving the problem of inability to take into account both safety and electrical performance.
Smart Images

Figure CN114156487B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a pole piece and a lithium ion battery, and relates to the technical field of lithium ion batteries. Background Art
[0002] Lithium-ion batteries are widely used in smart phones, laptops, Bluetooth, wearable devices and other fields due to their advantages such as high platform voltage, high energy density, no memory effect and long life. However, in some extreme cases, when lithium-ion batteries are mechanically damaged, such as needle puncture, heavy impact, etc., internal short circuits will occur, and a large amount of heat will be released in a short time, causing lithium-ion batteries to catch fire and fail, which poses a great safety hazard.
[0003] Providing a protective layer on the surface of the current collector helps to improve the safety of lithium-ion batteries. However, this will lead to a decrease in the electrical performance of the lithium-ion batteries. Therefore, how to strike a balance between the safety and electrical performance of lithium-ion batteries has received increasing attention. Summary of the invention
[0004] The present invention provides a pole piece for solving the problem that the safety and electrical performance of lithium-ion batteries cannot be taken into account at the same time.
[0005] The invention also provides a lithium ion battery with good safety and electrical performance.
[0006] A first aspect of the present invention provides a pole piece, comprising a substrate, the substrate comprising a current collector and a protective layer arranged on the surface of the current collector, and an active material layer is further arranged on the protective layer;
[0007] The protective layer includes 62%-96% of inactive material, 0.1%-8% of conductive agent and 3%-30% of binder in terms of mass percentage. The inactive material includes inorganic particles and a carbon layer coated on the surface of the inorganic particles, and the mass of the carbon layer is less than 10% of the mass of the inorganic particles.
[0008] According to one embodiment of the present invention, the mass of the carbon layer is 0.5%-5% of the mass of the inorganic particles.
[0009] According to one embodiment of the present invention, the inorganic particles include one or more of oxides, carbides, nitrides, and inorganic salts.
[0010] According to one embodiment of the present invention, the oxide is selected from one or more of aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, antimony sulfide, barium oxide, manganese oxide, silicon oxide, iron oxide, and iron oxide; the carbide includes metal carbide and / or non-metal carbide, the metal carbide includes one or more of titanium carbide, calcium carbide, chromium carbide, tantalum carbide, vanadium carbide, zirconium carbide, and tungsten carbide, and the non-metal carbide includes boron carbide and / or silicon carbide; the nitride includes metal nitride and / or non-metal nitride, the metal nitride includes one or more of lithium nitride, magnesium nitride, aluminum nitride, titanium nitride, and tantalum nitride, and the non-metal nitride includes at least one of boron nitride, phosphorus pentanenitride, and silicon nitride; the inorganic salt includes carbonate and / or sulfate.
[0011] According to one embodiment of the present invention, the thickness of the carbon layer is 1-100 nm.
[0012] According to one embodiment of the present invention, the D50 of the inactive material is ≤2 μm and the D90 is ≤5 μm.
[0013] According to one embodiment of the present invention, the D50 of the inactive material is 0.05-0.5 μm, and the D90 is 1-3 μm.
[0014] According to an embodiment of the present invention, the relationship between D50 of the inactive material and the thickness H1 of the protective layer satisfies H1≥2×D50.
[0015] According to an embodiment of the present invention, the relationship between the thickness H1 of the protective layer and the thickness H2 of the active material layer satisfies H1 / H2≤1 / 5.
[0016] A second aspect of the present invention provides a lithium-ion battery, comprising any of the above-mentioned pole pieces.
[0017] The implementation of the present invention has at least the following advantages:
[0018] 1. The pole piece provided by the present invention includes a protective layer. By controlling the mass fraction of each component in the protective layer and selecting carbon-coated inorganic particles, not only can the safety of lithium-ion batteries be effectively improved, especially when mechanical abuse occurs, the probability of lithium-ion batteries catching fire and failing can be reduced, and the pass rate of lithium-ion battery nail penetration tests can be increased, but also the electrical properties of the lithium-ion batteries can be kept basically unaffected, thereby solving the problem that the safety and electrical properties of lithium-ion batteries cannot be taken into account at the same time.
[0019] 2. The lithium-ion battery provided by the present invention has good safety and electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of the structure of a pole piece provided by an embodiment of the present invention;
[0021] Figure 2 A schematic structural diagram of a pole piece provided in yet another embodiment of the present invention.
[0022] Description of reference numerals:
[0023] 100-current collector;
[0024] 200-protective layer;
[0025] 300 - Active material layer. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] A first aspect of the present invention provides a pole piece, comprising a substrate, wherein the substrate comprises a current collector and a protective layer disposed on the surface of the current collector, and an active material layer is further disposed on the protective layer;
[0028] The protective layer includes 62%-96% of inactive material, 0.1%-8% of conductive agent and 3%-30% of binder in terms of mass percentage. The inactive material includes inorganic particles and a carbon layer coated on the surface of the inorganic particles, and the mass of the carbon layer is less than 10% of the mass of the inorganic particles.
[0029] The present invention provides a pole piece, comprising a substrate, the substrate comprising a current collector and a protective layer arranged on the surface of the current collector, and an active material layer is also arranged on the protective layer, for example, Figure 1 A schematic diagram of the structure of a pole piece provided in one embodiment of the present invention, Figure 2 A schematic diagram of the structure of a pole piece provided by another embodiment of the present invention is shown in FIG. Figure 1-2 As shown, the pole piece includes a current collector 100, which is a base metal in the pole piece for attaching a protective layer material, an active material, and other materials, and includes two surfaces for attaching a protective layer material, an active material, and other materials, specifically an upper surface and a lower surface. The protective layer 200 is located on the upper surface of the current collector 100, and an active material layer 300 is arranged on the protective layer 200. The length of the active material layer 300 can be greater than, equal to, or less than the length of the protective layer 200, that is, the active material layer 300 can be located on the protective layer 200 away from the upper surface of the current collector 100 (such as Figure 1), can also be divided into two parts, the first part of the active material layer 300 is located on the upper surface of the protective layer 200 away from the current collector, and the second part of the active material layer 300 is located on the part of the upper surface of the current collector where the protective layer is not provided (such as Figure 2 ), Figure 1-2 The configuration of the protective layer and the active material layer on the upper surface of the current collector is shown. The configuration of the other surface of the current collector 100 may be the same as or different from that of the upper surface. For example, the lower surface of the current collector 100 may be provided with a protective layer 200 and an active material layer 300, or only an active material layer 300. However, of the two surfaces of the current collector 100, at least one surface should be provided with a protective layer. Those skilled in the art may make the configuration according to actual needs, and the present invention does not impose any further restrictions on this.
[0030] In order to ensure that the electrical properties of the lithium-ion battery are basically not affected, the present invention selects inactive materials as the main components of the protective layer. Inactive materials refer to materials that do not participate in electrochemical reactions (as opposed to the function of active materials in the active material layer of the pole piece), which can reduce the impact of the protective layer on the cycle stability of the lithium-ion battery and take into account the electrical properties of the lithium-ion battery; as the main component of the protective layer 200, the inactive material also plays a role in supporting the protective layer. When the content of the inactive material is too low, the structural stability of the protective layer will be poor, and it will be damaged by the active material layer during the subsequent coating process of the active material layer, or the protective layer will be crushed by pressure during the rolling process of the pole piece. Therefore, the mass percentage of the inactive material should not be less than 62%; it can be understood that the protective layer 200, in addition to the inactive material, also includes a binder and a conductive agent. The binder is used to bond the inactive material, the conductive agent and other components together to form a coating, and to bond the protective layer to the current collector, thereby improving the stability of the protective layer and the bonding force between the protective layer and the current collector, thereby improving the stability and safety of the pole piece. When the content of the binder is too low, it cannot play a bonding role. It is not conducive to the good adhesion of the protective layer to the current collector. If the content of the binder is too high, it will easily make the pole piece brittle and reduce the compaction density, affecting the energy density of the lithium-ion battery. The conductive agent can construct an electronic conductive network, especially when the protective layer is located between the current collector and the active material layer, it can serve as an electronic path connecting the current collector and the active material layer, which is beneficial to the function of the current collector and improves the performance of the pole piece. If its content is too low, the conductivity of the protective layer will be insufficient, affecting the electrical properties of the pole piece. If the mass content of the conductive agent is too high, it will also affect the protective layer to a certain extent. The protective layer has a protective function for the pole piece. When an internal short circuit occurs, the protective layer has a high conductivity. When it contacts the pole piece of the other polarity, it will cause intense heat generation at the short circuit point, causing thermal runaway. Therefore, in order to take into account both the safety and electrical performance of the lithium-ion battery, the protective layer includes 62%-96% of inactive material, 0.1%-8% of conductive agent, and 3%-30% of binder according to mass percentage. That is, the total mass of the protective layer is 100%, the mass of the inactive material is 62%-96% of the total mass of the protective layer, and the mass of the conductive agent is 0.1%-8%, the mass of the binder is 3%-30% of the total mass of the protective layer; at the same time, the inventors found that the conductive network constructed by relying solely on the conductive agent cannot effectively guarantee the conductivity of the protective layer. In order to ensure that the electrical properties of the lithium-ion battery are not affected, the present invention selects carbon-coated inorganic particles as inactive materials. The carbon layer coated on the surface of the inorganic particles makes the inorganic particles conductive. In combination with the conductive agent in the protective layer, a more comprehensive conductive network can be constructed to avoid the problem of local conductivity loss caused by uneven conductive agents, improve the conductivity of the protective layer, and ensure the electrical properties of the lithium-ion battery. It can be understood that as the amount of carbon coating increases, the conductivity of the inactive material increases, but too high a carbon coating amount is not conducive to the safety performance of the battery. In order to take into account the safety and electrical properties of the lithium-ion battery, the mass of the carbon layer is less than 10% of the mass of the inorganic particles. The carbon coating process is a conventional process in the field, and the present invention will not be repeated here. The pole piece provided by the present invention includes a protective layer. By controlling the mass fraction of each component in the protective layer and selecting carbon-coated inorganic particles, the safety of lithium-ion batteries can be effectively improved, especially in the event of mechanical abuse, the probability of lithium-ion battery fire failure can be reduced, the pass rate of lithium-ion battery nail penetration test can be increased, and the electrical performance of the lithium-ion battery can be kept basically unaffected, solving the problem that the safety and electrical performance of lithium-ion batteries cannot be taken into account at the same time. .
[0031] In order to further take into account the safety and electrical performance of the lithium-ion battery, the mass of the carbon layer is 0.5%-5% of the mass of the inorganic particles.
[0032] In some embodiments, the inorganic particles include one or more of oxides, carbides, nitrides, and inorganic salts;
[0033] Further, the oxide is selected from at least one of aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, antimony sulfide, barium oxide, manganese oxide, silicon oxide, iron oxide, and ferroferric oxide; the carbide includes metal carbides and / or non-metal carbides, the metal carbide includes at least one of titanium carbide, calcium carbide, chromium carbide, tantalum carbide, vanadium carbide, zirconium carbide, and tungsten carbide, and the non-metal carbide includes boron carbide and / or silicon carbide; the nitride includes metal nitride and / or non-metal nitride, the metal nitride includes at least one of lithium nitride, magnesium nitride, aluminum nitride, titanium nitride, and tantalum nitride, and the non-metal nitride includes at least one of boron nitride, phosphorus pentanenitride, and silicon nitride; the inorganic salt includes carbonate and / or sulfate.
[0034] The materials and coating methods of the carbon layer can be carried out according to conventional techniques in the art. For example, the inorganic particles are mixed with a glucose solution, hydrothermally treated at a high temperature (150-200°C) for a period of time (2-5h), and then carbonized at a high temperature (600-800°C) in an inert gas atmosphere to obtain carbon-coated inorganic particles.
[0035] Those skilled in the art can reasonably select the ratio of inorganic particles to glucose to ensure that the mass of the carbon layer is less than 10% of the mass of the inorganic particles. In one embodiment, the thickness of the carbon layer is 1-100 nm.
[0036] Through research, it is found that when there are at least two layers of inactive material in the protective layer on the plane perpendicular to the current collector, it helps to further improve the protective effect of the protective layer. Therefore, the relationship between D50 of the inactive material and the thickness H1 of the protective layer satisfies H1≥2×D50. D50 is the particle size of the inactive material starting from the small particle size side and reaching 50% of the volume accumulation in the volume-based particle size distribution. The thickness H1 of the protective layer is the distance value from the surface of the current collector provided with the protective layer to the protective layer away from the surface of the current collector in the direction perpendicular to the current collector. When the two satisfy H1≥2×D50, it is beneficial to make the protective layer evenly distributed with at least two inactive materials in its thickness direction (the direction perpendicular to the surface of the current collector), which is equivalent to at least two layers of inactive material in the plane perpendicular to the current collector, thereby improving the protective effect of the protective layer and improving the safety of lithium-ion batteries.
[0037] In order to further improve the safety of lithium-ion batteries, small-particle inactive materials can be used. Specifically, the D50 of the inactive material is ≤2μm, and D90 is ≤5μm. The inactive material in this particle size range is not easy to fall off from the surface of the current collector during the nailing process, which helps to further improve the stability and safety of the pole piece. Furthermore, the D50 of the inactive material is 0.05-0.5μm, and the D90 is 1-3μm. D50 is the particle size of the inactive material starting from the small particle size side and reaching 50% of the volume accumulation in the volume-based particle size distribution; D90 is the particle size of the inactive material starting from the small particle size side and reaching 90% of the volume accumulation in the volume-based particle size distribution.
[0038] The binder and the conductive agent in the protective layer may be conventional materials in the art. For example, the binder includes one or more of polyvinylidene fluoride (PVDF), carboxylic acid-modified polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylates, and polyimides (PI), wherein the carboxylic acid-modified PVDF includes acrylic acid-modified PVDF; the conductive agent includes one or more of conductive carbon black, acetylene black, graphite, graphene, carbon nanotubes, and carbon nanofibers. Those skilled in the art may select suitable materials, mix them with inactive materials to obtain a protective layer slurry, apply them on the surface of the current collector, and dry them to obtain a protective layer.
[0039] The active material layer includes active materials for performing electrochemical reactions to provide capacity for the lithium-ion battery, while the protective layer itself does not provide capacity, but instead increases the weight and volume of the lithium-ion battery, causing a loss in the energy density of the lithium-ion battery. In order to further avoid the influence of the protective layer on the energy density of the lithium-ion battery, the thickness H1 of the protective layer should be controlled at a lower level than the thickness H2 of the active material layer. Specifically, the relationship between the thickness H1 of the protective layer and the thickness H2 of the active material layer satisfies H1 / H2≤1 / 5.
[0040] In the present invention, the above-mentioned electrode sheet can be a positive electrode sheet or a negative electrode sheet. When the electrode sheet is a positive electrode sheet, it includes a positive electrode collector, a protective layer and a positive electrode active material layer. When the electrode sheet is a negative electrode sheet, it includes a negative electrode collector, a protective layer and a negative electrode active material layer. The positive electrode collector can be an aluminum foil composed of aluminum as a main component, or a composite collector formed by pressing aluminum foil with other materials (such as polymer materials, etc.), or a composite collector including aluminum foil and a conductive carbon layer coated on the surface of the aluminum foil, etc., wherein the mass content of aluminum in the aluminum foil is generally not less than 95%; the negative electrode collector can be a copper foil or a nickel foil.
[0041] When the electrode sheet is a positive electrode sheet, the active material in the positive electrode active material layer is a positive electrode active material, for example, a positive electrode active material that provides lithium ions, specifically including a lithium positive electrode composite metal oxide (i.e., an inorganic material containing lithium), for example, including at least one of lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), and a ternary material, and the chemical formula of the ternary material can be LiNi x Co y Mn z O2, x+y+z=1. When the above-mentioned electrode sheet is a negative electrode sheet, the active material therein is a negative electrode active material, and the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase carbon microbeads (MCMB), silicon, silicon-carbon composite, silicon oxygen, lithium titanate, and lithium metal.
[0042] The active material layer also includes a binder and a conductive agent, which have the same function as the binder and conductive agent in the protective layer. The selection of the binder and conductive agent is as described above. The conductive agent and binder in the protective layer and the active material layer can be the same or different.
[0043] In addition, when the electrode sheet is a negative electrode sheet, the negative electrode active material layer may further include a dispersant, and the dispersant includes sodium carboxymethyl cellulose and the like.
[0044] Research has found that when an internal short circuit occurs in a lithium-ion battery, there will be multiple short circuit modes, and the internal short circuit caused by the contact between the positive electrode collector and the negative electrode is the most dangerous mode. Therefore, the above-mentioned electrode can be a positive electrode, that is, a protective layer is set on the surface of the positive electrode collector, while the negative electrode is not set with a protective layer.
[0045] The electrode provided by the present invention also includes an electrode ear, and the electrode ear can be set at a conventional electrode ear setting position in the art, for example, it can be set at the end or middle of the electrode. When the electrode is a positive electrode, the positive electrode ear can be aluminum foil; when the electrode is a negative electrode, the negative electrode ear can be nickel foil.
[0046] The pole piece provided by the present invention can be prepared by conventional methods in the field such as coating method. In specific implementation, the raw materials of the protective layer can be dispersed in a solvent, stirred evenly to prepare a protective layer slurry, and then the protective layer slurry is coated on the surface of the current collector, and the protective layer is formed after drying; the raw materials of the active material layer are dispersed in a solvent, stirred evenly to prepare an active material layer slurry, and then the active material layer slurry is coated on the surface of the protective layer away from the current collector or the area on the surface of the current collector where the protective layer is not provided, and the active material layer is formed after drying, rolling and other processes, and then the pole ear is placed on the surface of the current collector to obtain the pole piece.
[0047] In summary, the pole piece provided by the present invention includes a protective layer. By controlling the mass fraction of each component in the protective layer and selecting carbon-coated inorganic particles, not only can the safety of the lithium-ion battery be effectively improved, especially when mechanical abuse occurs, the probability of fire failure of the lithium-ion battery is reduced, and the pass rate of the nail penetration test of the lithium-ion battery is increased, but also the electrical performance of the lithium-ion battery is kept basically unaffected, thereby solving the problem that the safety and electrical performance of the lithium-ion battery cannot be taken into account at the same time.
[0048] A second aspect of the present invention provides a lithium-ion battery, comprising any of the above-mentioned pole pieces.
[0049] The present invention provides a lithium-ion battery, comprising the pole piece provided by the first aspect of the present invention. When the pole piece is a positive pole piece, the lithium-ion battery can be prepared by conventional technical means in combination with a conventional negative pole piece, a separator, and an electrolyte, wherein the separator comprises one or more of polyethylene (PE), polypropylene (PP), and polyimide, and the electrolyte comprises carbonate, carboxylic acid ester solvents, lithium salts, and appropriate additives. During the preparation process, the positive pole piece, the negative pole piece, and the separator are wound or stacked in sequence to form a battery core, and then the battery core is packaged with a packaging material such as an aluminum-plastic film and injected with an electrolyte, and the lithium-ion battery is prepared through charging and discharging. The lithium-ion battery provided by the present invention has good safety and electrical performance.
[0050] The present invention is further described below in conjunction with specific embodiments:
[0051] Example 1
[0052] The electrode sheet provided in this embodiment is a positive electrode sheet, comprising a current collector aluminum foil, a protective layer located on the surface of the current collector, and a positive electrode active material layer located on the protective layer away from the surface of the current collector, wherein:
[0053] The protective layer comprises 62 parts by mass of an inactive material, 30 parts by mass of acrylic acid-modified PVDF and 8 parts by mass of carbon black, wherein the inactive material is carbon-coated alumina, the mass of the carbon layer is 0.5% of the mass of the alumina, the D10 of the inactive material is 0.02 μm, the D50 is 0.3 μm, the D90 is 2 μm, and the thickness H1 of the protective layer is 2 μm;
[0054] The positive electrode active material layer includes 96 parts by mass of a positive electrode active material LCO, 2 parts by mass of a binder PVDF, and 2 parts by mass of a conductive agent carbon black. The thickness H2 of the positive electrode active material layer is 40 μm.
[0055] The preparation method of the electrode provided in this embodiment includes: mixing aluminum oxide, acrylic acid-modified PVDF and carbon black according to certain mass fractions, dispersing them in a solvent NMP, stirring them evenly to prepare a protective layer slurry, coating the protective layer slurry on the surface of the aluminum foil, and drying them to obtain a protective layer; mixing LCO, PVDF and carbon black according to certain mass fractions, dispersing them in a solvent NMP, stirring them evenly to prepare a positive electrode active material layer slurry, coating the positive electrode active material layer slurry on the surface of the protective layer away from the current collector, drying them to obtain a positive electrode active material layer, and rolling them to obtain a positive electrode sheet.
[0056] Example 2
[0057] The pole piece provided in this embodiment can refer to the embodiment 1, except that the protective layer includes 70 parts by mass of inactive material, 25 parts by mass of acrylic acid-modified PVDF and 5 parts by mass of carbon black.
[0058] Example 3
[0059] The pole piece provided in this embodiment can refer to the embodiment 1, except that the protective layer includes 80 parts by mass of inactive material, 15 parts by mass of acrylic acid-modified PVDF and 5 parts by mass of carbon black.
[0060] Example 4
[0061] The pole piece provided in this embodiment can refer to the embodiment 1, except that the protective layer includes 90 parts by mass of inactive material, 8 parts by mass of acrylic acid-modified PVDF and 2 parts by mass of carbon black.
[0062] Example 5
[0063] The pole piece provided in this embodiment can refer to the embodiment 1, except that the protective layer includes 96 parts by mass of inactive material, 3.9 parts by mass of acrylic acid-modified PVDF and 0.1 parts by mass of carbon black.
[0064] Example 6
[0065] The pole piece provided in this embodiment can refer to the embodiment 1, except that the protective layer includes 96 parts by mass of inactive material, 3 parts by mass of acrylic acid-modified PVDF and 1 part by mass of carbon black.
[0066] Example 7
[0067] The pole piece provided in this embodiment can refer to the embodiment 4, except that, in the inactive material, the mass of the carbon layer is 1% of the mass of the aluminum oxide.
[0068] Example 8
[0069] The pole piece provided in this embodiment can refer to the embodiment 4, except that, in the inactive material, the mass of the carbon layer is 2% of the mass of the aluminum oxide.
[0070] Example 9
[0071] The pole piece provided in this embodiment can refer to the embodiment 4, except that, in the inactive material, the mass of the carbon layer is 3% of the mass of the aluminum oxide.
[0072] Example 10
[0073] The pole piece provided in this embodiment can refer to the embodiment 4, except that, in the inactive material, the mass of the carbon layer is 4% of the mass of the aluminum oxide.
[0074] Embodiment 11
[0075] The pole piece provided in this embodiment can refer to the embodiment 4, except that, in the inactive material, the mass of the carbon layer is 5% of the mass of the aluminum oxide.
[0076] Comparative Example 1
[0077] The pole piece provided in this comparative example can refer to Example 1, except that the protective layer includes 50 parts by mass of inactive material, 45 parts by mass of acrylic acid-modified PVDF and 5 parts by mass of carbon black.
[0078] Comparative Example 2
[0079] The pole piece provided in this comparative example can refer to Example 1, except that the protective layer includes 62 parts by mass of inactive material, 20 parts by mass of acrylic acid-modified PVDF and 18 parts by mass of carbon black.
[0080] Comparative Example 3
[0081] The pole piece provided in this comparative example can refer to Example 1, except that the protective layer includes 92 parts by mass of inactive material, 2 parts by mass of acrylic acid-modified PVDF and 6 parts by mass of carbon black.
[0082] Comparative Example 4
[0083] The pole piece provided in this comparative example can refer to Example 1, except that the protective layer includes 92 parts by mass of inactive material and 8 parts by mass of acrylic acid-modified PVDF.
[0084] Comparative Example 5
[0085] The pole piece provided in this comparative example does not include a protective layer.
[0086] Comparative Example 6
[0087] The pole piece provided in this comparative example can refer to Example 4, except that the inactive material is aluminum oxide.
[0088] Comparative Example 7
[0089] The pole piece provided in this comparative example can refer to Example 4, except that, in the inactive material, the mass of the carbon layer is 10% of the mass of the aluminum oxide.
[0090] The positive electrode sheets provided in Examples 1-11 and Comparative Examples 1-7 were matched with negative electrode sheets and separators to prepare bare cells, which were packaged with aluminum-plastic films, injected with a certain amount of electrolyte and sealed, and subjected to chemical formation to obtain lithium-ion batteries, wherein the negative electrode sheet included a negative electrode current collector copper foil and a negative electrode active layer, and the negative electrode active layer included 96 parts by mass of artificial graphite, 1.5 parts by mass of styrene-butadiene rubber, 1.5 parts by mass of sodium carboxymethyl cellulose and 1 part by mass of carbon black.
[0091] Subsequently, the safety and electrical performance of the lithium ion batteries provided in Examples 1-11 and Comparative Examples 1-7 were tested. The test results are shown in Table 1. The test method is as follows:
[0092] (1) Nail penetration test
[0093] Take 10 lithium-ion batteries of each embodiment (comparative example), and place the fully charged batteries on the nail penetration test equipment, start the equipment, and make the nail (diameter 3mm) penetrate the center of the battery perpendicular to the battery plane at a speed of 130mm / s, stay for 10min and then withdraw. The battery is considered to have passed if it does not catch fire, and the number of lithium-ion batteries that have passed is counted.
[0094] (2) Rate performance test
[0095] The battery was discharged to 3.0V at a rate of 0.5C. After standing for 5 minutes, the battery was charged to the upper limit voltage at a rate of 0.5C, and then charged at a constant voltage with a cut-off current of 0.02C. After standing for 5 minutes, the battery was discharged to 3.0V at a rate of 0.2C, and the capacity was C0. After standing for 5 minutes, the battery was charged to the upper limit voltage at a rate of 0.5C, and then charged at a constant voltage with a cut-off current of 0.02C. After standing for 5 minutes, the battery was discharged to 3.0V at a rate of 0.5C, and the capacity was C1. C1 / C0 is the discharge capacity ratio of 0.5C / 0.2C, which is used to evaluate the rate discharge capability.
[0096] (3) Lithium-ion battery energy density test
[0097] The energy density of lithium-ion batteries is ED = E / V, where E is the discharge energy of the battery. The test method is to fully charge the battery and then discharge it at 0.2C until it reaches 3.0V. The discharge energy is E. V is the volume of the battery, which is obtained by measuring the length, width, and height.
[0098] The energy density loss rate ΔED is the energy density ED5 of the lithium ion battery of comparative example 5 and the energy density ED of the lithium ion battery of the corresponding embodiment (comparative example) n The difference between ED5 and ED5 / the energy density ED5 of the lithium-ion battery of Comparative Example 5, that is, △ED = (ED5-ED n ) / ED5.
[0099] Table 1
[0100]
[0101] Compared with the data provided in Comparative Example 5, providing a protective layer helps to improve the safety of the lithium-ion battery, but the energy density is lost to varying degrees; according to the data provided in Examples 1-6 and Comparative Examples 1-4, it can be seen that controlling the mass fraction of each component in the protective layer within the range provided by the present invention helps to take into account both the safety and electrical performance of the lithium-ion battery; according to the data provided in Examples 7-11 and Comparative Example 6, it can be seen that the use of carbon-coated inorganic particles helps to improve the rate performance of the lithium-ion battery. According to the data provided in Examples 7-11 and Comparative Example 7, when the carbon coating amount on the surface of the inorganic particles exceeds 10%, the safety performance of the lithium-ion battery is significantly reduced.
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A pole piece, characterized in that: The invention comprises a substrate, wherein the substrate comprises a current collector and a protective layer arranged on the surface of the current collector, and an active material layer is further arranged on the protective layer; The protective layer comprises 62%-96% of inactive material, 0.1%-8% of conductive agent and 3%-30% of binder in terms of mass percentage, the inactive material comprises inorganic particles and a carbon layer coated on the surface of the inorganic particles, and the mass of the carbon layer is less than 10% of the mass of the inorganic particles; the inorganic particles are selected from one or more of oxides, carbides, nitrides and inorganic salts; the oxide is selected from one or more of aluminum oxide, titanium oxide, magnesium oxide, zirconium oxide, antimony sulfide, barium oxide, manganese oxide, silicon oxide, iron oxide and ferroferric oxide; The carbide is selected from metal carbides and / or non-metal carbides, the metal carbide is selected from one or more of titanium carbide, calcium carbide, chromium carbide, tantalum carbide, vanadium carbide, zirconium carbide, and tungsten carbide, and the non-metal carbide is selected from boron carbide and / or silicon carbide; the nitride is selected from metal nitrides and / or non-metal nitrides, the metal nitride is selected from one or more of lithium nitride, magnesium nitride, aluminum nitride, titanium nitride, and tantalum nitride, and the non-metal nitride is selected from at least one of boron nitride, phosphorus pentanenitride, and silicon nitride; the inorganic salt is selected from carbonates and / or sulfates.
2. The pole piece according to claim 1, characterized in that: The mass of the carbon layer is 0.5%-5% of the mass of the inorganic particles.
3. The pole piece according to claim 1, characterized in that: The thickness of the carbon layer is 1-100 nm.
4. The pole piece according to claim 1, characterized in that: The inactive material has a D50≤2μm and a D90≤5μm.
5. The pole piece according to claim 1 or 4, characterized in that: The inactive material has a D50 of 0.05-0.5 μm and a D90 of 1-3 μm.
6. The pole piece according to claim 1, characterized in that: The relationship between D50 of the inactive material and the thickness H1 of the protective layer satisfies H1 ≥ 2×D50.
7. The pole piece according to claim 1 or 6, characterized in that: The relationship between the thickness H1 of the protective layer and the thickness H2 of the active material layer satisfies H1 / H2≤1 / 5.
8. A lithium ion battery, characterized in that: A pole piece comprising any one of claims 1 to 7.
Citation Information
Patent Citations
Electrode pole plate, electrochemical device and safety coating layer
CN109755463A
Electrode pole plate, electrochemical device and safety coating layer
CN109755468A
Lithium ion battery pole piece and lithium ion battery
CN203218375U